Enhancing cassava N/K use efficiency through Fenlong tillage: driving forces of soil porosity improvement and aerobic bacteria enrichment - Li, Guilong; Peng, Xiaohui; Gan, Li; Huang, Yuanhang; Qin, Fengyan; Li, Liangwu; Zhou, Jia; Yang, Weixian; Shen, Zhangyou; Wei, Maogui (Frontiers in Microbiology, 2026)
Cassava (Manihot esculenta Crantz) is continuously cultivated using the conventional tillage (CT) method in southern China, resulting in increasingly compact soil and decreased yield and fertilizer use efficiency (FUE) year after year. Compared to CT, Fenlong (FL) tillage, which uses spiral drill bits to replace traditional ploughshares, has been found to significantly increase crop yield ranged from 10% to 50% such as cassava, sugarcane, maize, cotton, rice, and wheat without extra fertilizer input. However, previous studies have primarily elucidated the mechanism behind yield increases from FL by examining changes in soil physicochemical properties and microbial communities. Research on how it enhances FUE remains scarce. Thus, the current study aimed to investigate how FL influences both cassava yield and FUE, which would be of great significance for implementing the plan “increasing crop yield without increasing fertilizer” released by the Ministry of Agriculture of China. Results indicated that the soil porosity of the FL treatment was 2.07 to 38.37% higher than that of the CT group. Moreover, compared with CT, the soil bulk density under FL treatment decreased by 0.64% to 12.07% across different soil layers, with significant reductions observed in the 11 ~ 30 cm layers in 2019 and the 21 ~ 30 cm layer in 2020. The relative abundance of aerobic bacteria (i.e., Gemmatimonadaceae [Family] and Tumebacillus [Genus] in 2019; Micromonosporaceae [Family], Tumebacillus [Genus], Conexibacter [Genus], and Acidobacteriales [Order] in 2020) in the FL group was higher than that in CT. The FL treatment significantly outperformed CT, with increases ranging from 9.04 to 135.81% in tuberous root yield, 11.51 to 62.07% in FUE-N, and 21.75 to 40.76% in FUE-K, while the fertilization regime of N 118.2 kg.ha−1, P2O5 29.4 kg.ha−1, and K2O 61.9 kg.ha−1 under FL managed to reach an ideal balance between cassava yield and FUE. Structural equation modeling revealed that FL tillage improves soil conditions for cassava and aerobic bacteria through deep soil fragmentation. This promotes soil fertility, facilitates deeper root penetration for enhanced nutrient and water uptake, and ultimately leads to higher yield and FUE compared to CT.